Determinants of Treatment Delay in Drug-Resistant Tuberculosis Patients in Banten Province in 2020 - Oktarini, Ria; Widiyaningsih, Cicilia; Sunita, Anna (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Indonesia is currently ranked 2nd with the most tuberculosis cases in the world, after India and China. is ranked 2nd with the most tuberculosis sufferers in the world, after India and China. Tuberculosis control in Indonesia faces many challenges, one of which is the increase in patients with drug-resistant tuberculosis (DR TB). In 2019, the number of tuberculosis sufferers in Indonesia reached 543,874 cases, with drug-resistant tuberculosis cases reaching 11,463 (2.1%). Banten is one of the provinces with the highest number of Tuberculosis sufferers in Java, which is 223 people per 100,000 population, with a national TB rate of 203 people per 100,000 population, of which only 58.3% take medication regularly. This study aims to determine the determinants of treatment delay in drug-resistant tuberculosis patients in Banten province in 2020. The study design was a retrospective cohort. The sampling technique was a total sampling of the list of DR TB cases at South Tangerang city General Hospital and dr. Drajat Prawiranegara Serang. Secondary data search was carried out on the TB Information System (SITB) and patient medical records. The study population was 114 respondents, obtained 90 respondents who fit the inclusion and exclusion criteria. Univariate, bivariate analysis with chi-square test and multivariate with logistic regression statistical test were performed to obtain a fit final model. The results of the bivariate analysis showed a significant relationship between age (p=0.030) and employment status (p=0.003). The final multivariate model, showing employment status with delayed treatment (p = 0.008), with OR 18,788 (95% CI: 2,122 – 166.329), meaning that respondents who have jobs have 18.8 times risk for late treatment compared to respondents who do not have jobs after being controlled by variables of age, gender, history of TB, and education level. The researcher concludes that the determinants of delay in treatment of DR TB patients in Banten province in 2020 are employment status and age. It is recommended that the Banten Provincial Health Office can coordinate cross sectors, to ensure the treatment of DR TB patients until they are cured. Keywords: epidemiology, tuberculosis, drug-resistant